2015
DOI: 10.1002/ajh.23976
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular risk assessments in chronic myeloid leukemia allow identification of patients at high risk of cardiovascular events during treatment with nilotinib

Abstract: Cardiovascular risk assessments in chronic myeloid leukemia allow identification of patients at high risk of cardiovascular events during treatment with nilotinibTo the Editor Nilotinib, a second-generation tyrosine kinase inhibitor, has been approved at the dose of 300 mg bis in die (BID) for newly diagnosed chronic phase chronic myeloid leukemia patients and at the dose of 400 mg BID for chronic or accelerated phase patients with resistance or intolerance to imatinib [1]. In the last few years, several commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
5
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 10 publications
3
5
0
2
Order By: Relevance
“… 36 Improvement in oral intake may account for the significantly higher mean weight and BMI in the imatinib-treated CML group than in the imatinib-naive CML group. This observation is somewhat similar to the findings of Breccia et al, 37 who reported that 50% of CML patients treated with TKIs had a normal BMI. In addition, the release of cachexin and other cytokines can lead to weight loss in CML groups.…”
Section: Discussionsupporting
confidence: 92%
“… 36 Improvement in oral intake may account for the significantly higher mean weight and BMI in the imatinib-treated CML group than in the imatinib-naive CML group. This observation is somewhat similar to the findings of Breccia et al, 37 who reported that 50% of CML patients treated with TKIs had a normal BMI. In addition, the release of cachexin and other cytokines can lead to weight loss in CML groups.…”
Section: Discussionsupporting
confidence: 92%
“…In one larger retrospective study involving 81 patients receiving nilotinib, the incidence of AMI was 7.5% ( 23 ). In the analysis of 82 patients treated with nilotinib, the cumulative incidence of atherosclerotic events at 48 months was 8.5%, which was higher among patients with elevated cardiovascular risk ( 36 ). In a study that evaluated the effectiveness of ponatinib in the treatment of CML, treatment-related adverse cardiovascular events were observed in 2% ( 37 ).…”
Section: Cardiotoxicity: Chemotherapy and Radiotherapymentioning
confidence: 97%
“…Высокий риск ишемических событий может сохраняться и после отмены препаратов, в том числе на фоне оптимальной терапии [194,195,196]. Перечисленные осложнения возможны при отсутствии у пациента факторов риска атеросклероза или сердечно-сосудистой патологии в анамнезе, однако при их наличии вероятность неблагоприятных событий возрастает [197]. В качестве возможных механизмов сосудистой токсичности рассматриваются подавление неоангиогенеза, дисфункция и гибель эндотелиальных клеток [198].…”
Section: ингибиторы тирозинкиназ подавляющие активность Bcr-abl онкоп...unclassified